Enumeration of Mycobacterium avium subsp. paratuberculosis by quantitative real-time PCR, culture on solid media and optical densitometry - Kralik, Petr; Beran, Vladimir; Pavlik, Ivo (BMC research notes, 2012)
BACKGROUND: Different approaches are used for determining the number of Mycobacterium avium subsp. paratuberculosis (MAP) cells in a suspension. The majority of them are based upon culture (determination of CFU) or visual/instrumental direct counting of MAP cells. In this study, we have compared the culture method with a previously published F57 based quantitative real-time PCR (F57qPCR) method, to determine their relative abilities to count the number of three different MAP isolates in suspensions with the same optical densities (OD). McFarland turbidity standards were also compared with F57qPCR and culture, due to its frequent inclusion and use in MAP studies. FINDINGS: The numbers of MAP in two-fold serial dilutions of isolates with respective OD measurements were determined by F57qPCR and culture. It was found that culture provided lower MAP CFU counts by approximately two log10, compared to F57qPCR. The McFarland standards (as defined for E. coli) showed an almost perfect fit with the enumeration of MAP performed by F57qPCR. CONCLUSIONS: It is recommended to use culture and/or qPCR estimations of MAP numbers in experiments where all subsequent counts are performed using the same method. It is certainly not recommended the use of culture as the standard for qPCR experiments and vice versa.
Keywords: Cattle; Animals; skot; Real-Time Polymerase Chain Reaction; bakteriální nálož; feces; Feces; Escherichia coli; DNA bakterií; DNA, Bacterial; Densitometry; Culture Media; Mycobacterium avium subsp. paratuberculosis; nemoci skotu; denzitometrie; Cattle Diseases; kultivační média; Paratuberculosis; zvířata; kvantitativní polymerázová řetězová reakce; Bacterial Load; paratuberkulóza